Impact of Work-Life Balance on Mental Health - Xavier, Kingston (Digital Repository of Theses, 2024)
The study explores the relationship between work-life balance and mental health, highlighting the importance of maintaining a balance between personal and professional life. The modern work environment, with constant connectivity and remote work capabilities, has blurred the lines between personal and professional spheres, leading to chronic stress, anxiety, and burnout. The research found that better work-life balance reduces stress, anxiety, and depression, and that the prevalence of mental health disorders in employed people is strongly influenced by work-life balance. The study also found that work-life balance affects mental health differently for men and women, with gender playing a moderate role. Higher organizational support was found to mitigate the detrimental effects of poor work-life balance on mental health. The lack of a healthy work-life balance can lead to severe mental health issues, such as stress, anxiety, and depression, which are exacerbated by the modern work environment's demands. A healthy work-life balance offers numerous benefits, such as improved mental health, increased job satisfaction, and enhanced productivity. The research underscores the broader social implications of work-life balance, including the impact on familial relationships and societal cohesion. Employers should foster a culture that values work-life balance by offering flexible working arrangements, access to mental health services, and open discussions about mental health. Policymakers should enforce regulations that limit excessive working hours and provide incentives for businesses that implement work-life balance programs. In conclusion, the study emphasizes the importance of a balanced approach to work and personal life for maintaining mental health and overall well-being.